Pemberdayaan Santri dan Masyarakat Sekitar Pondok Pesantren Rhaudul Ulum Sakatiga, Ogan Ilir Melalui Diversifikasi Produk Perikanan - Herpandi Herpandi; Indah Widiastuti; Ace Baehaki; Sabri Sudirman; Gama Dian Nugroho; Wulandari (Universitas Mathla'ul Anwar Banten, 2022)
Diversification of fisheries product processing is a way of processing raw materials into final products that have various types. Fish raw materials can be processed into various products such as fish crackers, fish nuggets and fish balls. The product manufacturing training activity at the Rhaudaul Ulum Sakatiga Islamic boarding school went well, the students and the surrounding community were enthusiastic about the training in making fishery diversification products. Diversified fishery products made include mackerel fish balls, catfish nuggets and cork fish crackers. Participants' interest was shown by the participants actively asking questions and participating in demonstrations and actively participating during the training process.